Intramolecular hydroamination of alkynic sulfonamides catalyzed by a gold–triethynylphosphine complex: Construction of azepine frameworks by 7-exo-dig cyclization - Ito, Hideto; Harada, Tomoya; Ohmiya, Hirohisa; Sawamura, Masaya (Beilstein Journal of Organic Chemistry, 2011)
The gold-catalyzed, seven-membered ring forming, intramolecular hydroamination of alkynic sulfonamides has been investigated. The protocol, with a semihollow-shaped triethynylphosphine as a ligand for gold, allowed the synthesis of a variety of azepine derivatives, which are difficult to access by other methods. Both alkynic sulfoamides with a flexible linear chain and the benzene-fused substrates underwent 7-exo-dig cyclization to afford the nitrogen-containing heterocyclic seven-membered rings, such as tetrahydroazepine and dihydrobenzazepine, in good yields.
Keywords: azepine; cyclization; gold catalyst; hydroamination; triethynylphosphine

(untitled) - Uyeo, S.; Irie, H.; Harada, H. (Chem. Pharm. Bull., 1967)

(untitled) - Harada, H.; Irie, H.; Masaki, N.; Osaki, K.; Uyeo, S. (Chem. Commun. (London), 1967)

(untitled) - Götz, M.; Bögri, T.; Gray, A. H.; Strunz, G. M. (Tetrahedron, 1968)

(untitled) - Lin, W.-H.; Ye, Y.; Xu, R.-S. (J. Nat. Prod., 1992)

(untitled) - Pilli, R. A.; Ferreira de Oliveira, M. C. (Nat. Prod. Rep., 2000)

(untitled) - Wipf, P.; Rector, S. R.; Takahashi, H. (J. Am. Chem. Soc., 2002)

(untitled) - Alibés, R.; Figueredo, M. (Eur. J. Org. Chem., 2009)

(untitled) - Paudler, W. W.; Kerley, G. I.; McKay, J. (J. Org. Chem., 1963)

(untitled) - Weinreb, S. M.; Semmelhack, M. F. (Acc. Chem. Res., 1975)

The Alkaloids: Chemistry and Pharmacology - Huang, L.; Xue, Z. (Cephalotaxus alkaloids, 1984)

The Alkaloids: Chemistry and Biology - Jalil Miah, M. A.; Hudlicky, T.; Reed, J. W. (Cephalotaxus Alkaloids, 1998)

(untitled) - Isono, N.; Mori, M. (J. Org. Chem., 1995)

(untitled) - Kumar, S.; Dare, L.; Vasko-Moser, J. A.; James, I. E.; Blake, S. M.; Rickard, D. J.; Hwang, S.-M.; Tomaszek, T.; Yamashita, D. S.; Marquis, R. W.; Oh, H.; Jeong, J. U.; et al. (Bone, 2007)

(untitled) - Yamashita, D. S.; Marquis, R. W.; Xie, R.; Nidamarthy, S. D.; Oh, H.-J.; Jeong, J. U.; Erhard, K. F.; Ward, K. W.; Roethke, T. J.; Smith, B. R.; Cheng, H.-Y.; Geng, X.; et al. (J. Med. Chem., 2006)

(untitled) - Wang, H.; Matsuhashi, H.; Doan, B. D.; Goodman, S. N.; Ouyang, X.; Clark, W. M., Jr (Tetrahedron, 2009)

(untitled) - Goodman, S. N.; Dai, Q.; Wang, J.; Clark, W. M., Jr (Org. Process Res. Dev., 2011)

(untitled) - Müller, T. E.; Beller, M. (Chem. Rev., 1998)

(untitled) - Müller, T. E.; Hultzsch, K. C.; Yus, M.; Foubelo, F.; Tada, M. (Chem. Rev., 2008)

(untitled) - Hashmi, A. S. K. (Chem. Rev., 2007)

(untitled) - Li, Z.; Brouwer, C.; He, C. (Chem. Rev., 2008)

(untitled) - Arcadi, A. (Chem. Rev., 2008)

(untitled) - Gorin, D. J.; Sherry, B. D.; Toste, F. D. (Chem. Rev., 2008)

(untitled) - Patil, N. T.; Yamamoto, Y. (Chem. Rev., 2008)

(untitled) - Hashmi, A. S. K.; Rudolph, M. (Chem. Soc. Rev., 2008)

(untitled) - Marion, N.; Nolan, S. P. (Chem. Soc. Rev., 2008)

(untitled) - Shapiro, N. D.; Toste, F. D. (Synlett, 2010)

(untitled) - Corma, A.; Leyva-Pérez, A.; Sabater, M. J. (Chem. Rev., 2011)

(untitled) - Krause, N.; Winter, C. (Chem. Rev., 2011)

(untitled) - Shu, X.-Z.; Liu, X.-Y.; Xiao, H.-Q.; Ji, K.-G.; Guo, L.-N.; Liang, Y.-M. (Adv. Synth. Catal., 2008)

(untitled) - Enomoto, T.; Obika, S.; Yasui, Y.; Takemoto, Y. (Synlett, 2008)

(untitled) - Ye, D.; Wang, J.; Zhang, X.; Zhou, Y.; Ding, X.; Feng, E.; Sun, H.; Liu, G.; Jiang, H.; Liu, H. (Green Chem., 2009)

(untitled) - Peng, H. M.; Zhao, J.; Li, X. (Adv. Synth. Catal., 2009)

(untitled) - Ye, D.; Zhang, X.; Zhou, Y.; Zhang, D.; Zhang, L.; Wang, H.; Jiang, H.; Liu, H. (Adv. Synth. Catal., 2009)

(untitled) - Liu, X.-Y.; Che, C.-M. (Org. Lett., 2009)

(untitled) - Yamane, Y.; Liu, X.; Hamasaki, A.; Ishida, T.; Haruta, M.; Yokoyama, T.; Tokunaga, M. (Org. Lett., 2009)

(untitled) - Zhou, Y.; Feng, E.; Liu, G.; Ye, D.; Li, J.; Jiang, H.; Liu, H. (J. Org. Chem., 2009)

(untitled) - Enomoto, T.; Girard, A.-L.; Yasui, Y.; Takemoto, Y. (J. Org. Chem., 2009)

(untitled) - Han, Z.-Y.; Xiao, H.; Chen, X.-H.; Gong, L.-Z. (J. Am. Chem. Soc., 2009)

(untitled) - Wilckens, K.; Uhlemann, M.; Czekelius, C. (Chem.–Eur. J., 2009)

(untitled) - Hirano, K.; Inaba, Y.; Watanabe, T.; Oishi, S.; Fujii, N.; Ohno, H. (Adv. Synth. Catal., 2010)

(untitled) - Zeng, X.; Kinjo, R.; Donnadieu, B.; Bertrand, G. (Angew. Chem., Int. Ed., 2010)

(untitled) - Hashmi, A. S. K.; Ramamurthi, T. D.; Rominger, F. (Adv. Synth. Catal., 2010)

(untitled) - Patil, N. T.; Singh, V.; Konala, A.; Mutyala, A. K. (Tetrahedron Lett., 2010)

(untitled) - Gimeno, A.; Medio-Simón, M.; Ramírez de Arellano, C.; Asensio, G.; Cuenca, A. B. (Org. Lett., 2010)

(untitled) - Wang, C.; Han, Z.-Y.; Luo, H.-W.; Gong, L.-Z. (Org. Lett., 2010)

(untitled) - Zhang, L.; Ye, D.; Zhou, Y.; Liu, G.; Feng, E.; Jiang, H.; Liu, H. (J. Org. Chem., 2010)

(untitled) - Kothandaraman, P.; Rao, W.; Foo, S. J.; Chan, P. W. H. (Angew. Chem., Int. Ed., 2010)

(untitled) - Demir, A. S.; Emrullahoğlu, M.; Buran, K. (Chem. Commun., 2010)

(untitled) - Monge, D.; Jensen, K. L.; Franke, P. T.; Lykke, L.; Jørgensen, K. A. (Chem.–Eur. J., 2010)

(untitled) - Arcadi, A.; Abbiati, G.; Rossi, E. (J. Organomet. Chem., 2011)

(untitled) - Kitahara, H.; Sakurai, H. (J. Organomet. Chem., 2011)

(untitled) - Zulys, A.; Dochnahl, M.; Hollmann, D.; Löhnwitz, K.; Herrmann, J.-S.; Roesky, P. W.; Blechert, S. (Angew. Chem., Int. Ed., 2005)

(untitled) - Yu, Y.; Stephenson, G. A.; Mitchell, D. (Tetrahedron Lett., 2006)

(untitled) - Liu, J.; Shen, M.; Zhang, Y.; Li, G.; Khodabocus, A.; Rodriguez, S.; Qu, B.; Farina, V.; Senanayake, C. H.; Lu, B. Z. (Org. Lett., 2006)

(untitled) - Ochida, A.; Ito, H.; Sawamura, M. (J. Am. Chem. Soc., 2006)

(untitled) - Ito, H.; Makida, Y.; Ochida, A.; Ohmiya, H.; Sawamura, M. (Org. Lett., 2008)

(untitled) - Ito, H.; Ohmiya, H.; Sawamura, M. (Org. Lett., 2010)

(untitled) - Ochida, A.; Sawamura, M. (Chem.–Asian J., 2007)

(untitled) - Duan, H.; Sengupta, S.; Petersen, J. L.; Akhmedov, N. G.; Shi, X. (J. Am. Chem. Soc., 2009)